KORELASI KADAR HEMOGLOBIN DENGAN LAJU FILTRASI GLOMERULUS PADA PASIEN GAGAL GINJAL KRONIK STADIUM 3 DAN 4 - Siska Monika Faridz; Syuhada Syuhada; Akhmad Kheru (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Background Chronic kidney disease was one of the 18 causes of death in 2010. Anemia is a complication of CKD that often occurs even earlier than other complications. Renal dysfunction results in reduced creatinine filtration ability and an increase in serum creatinine.Purpose of this study was to determine the correlation between hemoglobin levels and glomerular filtration rate in patients with stage 3 and 4 chronic kidney failure at Abdul Moeloek Hospital in Bandar Lampung in 2020.Methods This type of research is quantitative with retrospective analytical methods. The research was conducted at the Medical Records section of the Abdul Moeloek Hospital Bandar Lampung from December 2020 to completion. The number of samples as many as 36 people using the person correlation statistical test. Result Based on the results of the Pearson correlation analysis between hemoglobin levels and glomerular filtration rate in patients with stage 3 and 4 chronic kidney failure at Abdul Moeloek Hospital, Bandar Lampung, 2020 shows a relationship with r (correlation coefficient) of, 688. This data shows that there is a positive relationship between hemoglobin levels and glomerular filtration rate in patients with stage 3 and 4 chronic renal failure at Abdul Moeloek Hospital, Bandar Lampung in 2020, the relationship is categorized as a strong relationship (0.61-0.80). . The P-value = 0,000 indicates a significant relationship between hemoglobin levels and glomerular filtration rate in patients with stage 3 and 4 chronic renal failure at Abdul Moeloek Hospital Bandar Lampung in 2020. Conclusion There is a correlation between hemoglobin levels and glomerular filtration rate in patients with stage chronic renal failure. 3 and 4 at Abdul Moeloek Hospital in Bandar Lampung in 2020Suggestions for the Community The community is expected to seek information regarding the prevention of kidney failure and then start living a healthy lifestyle to avoid kidney failure. For patients with kidney failure, they should regularly check themselves to the nearest health facility and check creatinine and hemoglobin levels. Keywords: Chronic renal failure, Creatinine, Hemoglobin, Glumerular Filtration Rate ABSTRAK Latar Belakang Penyakit ginjal kronik salah satu penyebab kematian ke-18 pada tahun 2010. Anemia merupakan salah satu komplikasi PGK yang sering terjadi bahkan terjadi lebih awal dari komplikasi lainnya. Disfungsi ginjal mengakibatkan kemampuan filtrasi kreatinin akan berkurang dan akan terjadi peningkatan pada kreatinin serum.Tujuan penelitian ini untuk mengetahui korelasi antara kadar hemoglobin dengan laju filtrasi glomerulus pada pasien gagal ginjal kronik stadium 3 dan 4 di Rumah Sakit Abdul Moeloek Bandar Lampung Tahun 2020.Metode Jenis penelitian ini adalah kuantitatif dengan metode analitik retrospektif. Penelitian dilakukan di bagian Rekam Medik Rumah Sakit Abdul Moeloek Bandar Lampung pada bulan Desember 2020 hingga selesai. jumlah sampel sebanyak 36 orang menggunakan uji statistic korelasi person. Berdasarkan hasil analisi korelasi Pearson antara kadar hemoglobin dengan laju filtrasi glomerulus pada pasien gagal ginjal kronik stadium 3 dan 4 di Rumah Sakit Abdul Moeloek Bandar Lampung Tahun 2020 menunjukan adanya hubungan dengan r (koefisien korelasi) sebesar ,688.Hasil Data ini menunjukan bahwa terdapat hubungan positif antara kadar hemoglobin dengan laju filtrasi glomerulus pada pasien gagal ginjal kronik stadium 3 dan 4 di Rumah Sakit Abdul Moeloek Bandar Lampung Tahun 2020 hubunganya dikategorikan sebagai hubungan yang kuat (strong) (0,61-0,80). Nilai P-value = 0,000 menunjukan hubungan signifikan antara kadar hemoglobin dengan laju filtrasi glomerulus pada pasien gagal ginjal kronik stadium 3 dan 4 di Rumah Sakit Abdul Moeloek Bandar Lampung Tahun 2020.Kesimpulan Terdapat korelasi antara kadar hemoglobin dengan laju filtrasi glomerulus pada pasien gagal ginjal kronik stadium 3 dan 4 di Rumah Sakit Abdul Moeloek Bandar Lampung Tahun 2020.Saran Bagi Masyarakat Masyarakat diharapkan mencari informasi terkait penegahan penyakit gagal ginjal kemudian mulai menjalani gaya hidup sehat agar terhindar dari penyakit gagal ginjal. Bagi penderita gagal ginjal agar rutin memeriksanakn diri ke fasilitas kesehatan terdekat dan memeriksakan kadar kreatinin serta hemoglobin. Kata Kunci : Gagal ginjal kronik, Kreatinin, Hemoglobin, Laju Filtrasi Glumerulus